2000
DOI: 10.1081/prg-100100132
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcome of Preeclamptic Pregnancies: The Potential Roles of Factor v Leiden Mutation and 5,10 Methylenetetrahydrofolate Reductase

Abstract: Although the frequency of Factor V Leiden mutation appears to be significantly higher among preeclamptic women, the mechanism of pathogenesis and potential influence on perinatal outcomes is not yet well understood. Relatively high rates of HELLP syndrome among those with Factor V Leiden mutation suggest that this thrombogene mutation may play a significant role in hemostatic system activation. Our results suggest that the role of MTHFR polymorphism and other factors such as folic acid supplementation will req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 19 publications
6
62
3
3
Order By: Relevance
“…We had similar findings in our previous study of 120 pre-eclamptic women in 2000. 7 In the present study, however, there was a substantial difference between the incidence of MTHFR 677TT genotype among HELLP syndrome patients compared to the other two study groups.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…We had similar findings in our previous study of 120 pre-eclamptic women in 2000. 7 In the present study, however, there was a substantial difference between the incidence of MTHFR 677TT genotype among HELLP syndrome patients compared to the other two study groups.…”
Section: Discussioncontrasting
confidence: 73%
“…The severe pre-eclamptic and HELLP syndrome patients were diagnosed according to the recommendations of the ACOG. 7 Briefly, patients in the severe PE group had systolic BP4160 mm Hg and diastolic BP 490 mm Hg with significant proteinuria and intrauterine growth restriction (IUGR). IUGR was diagnosed in neonates when their birth weight was below 10 percentile for gestational age by weight based on Hungarian population tables.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, the meta-analysis by Xia et al (95) reported that the TT genotype compared with the CC and CT genotypes carried a significantly greater risk of preeclampsia (by 76%) among Asian women only, whereas in Caucasian women this increased risk was not evident. It is worth noting however that a much greater number of large-scale studies in this area have been conducted within Asian populations with far fewer studies conducted in Caucasian populations; a factor that limits Sohda et al (87) 425 Japan 2·5 (1·3, 4·8) Grandone et al (88) 225 Italy 1·8 (1·0, 3·5) Kupferminc (96) 144 Israel 2·9 (1·0, 8·5) Powers et al (97) 237 Caucasian women 1·28 (0·58, 2·79) Kobashi et al (98) 316 Japan 0·68 (0·30, 1·55) Laivuori et al (99) 216 Finland 0·50 (0·14, 1·77) Rigo et al (100) 221 Caucasian women 1·13 (0·38, 3·37) Morrison et al (101) 404 Scotland 1·00 (0·55, 1·82) Prasmusinto et al (102) 112 Germany and Croatia 0·28 (0·03, 2·47) Pegoraro et al (103) 609 South African (Black) 0·62 (0·06, 6·90) Perez-Mutul et al (91) 325 Mexico 0·94 (0·59, 1·49) Williams et al (104) 304 Peru 1·6 (0·7, 3·8) Yilmaz et al (105) 111 Turkey 0·84 (0·26, 2·67) Also-Rallo et al (79) 165 Spain 0·73 (0·31, 1·76) Hernandez-Diaz et al (86) 154 USA/Canada 3·0 (1·2, 7·7) Stiefel et al (106) 584 Spain 0·92 (0·50, 1·71) the extent to which different populations can be compared. An additional limitation is that genotype-driven recruitment is generally not undertaken in these studies, a feature that is reflected by the relatively small numbers of pregnant women with the TT genotype being investigated and these raised the concern that many such studies may be statistically underpowered.…”
Section: Role Of the Mthfr Genotype In Determining The Risk Of Hypertmentioning
confidence: 99%